Nitric Oxide Synthase Activity Correlates with OGG1 in Ozone-Induced Lung Injury Animal Models - Zhang, Suqin; Li, Jianhua; Li, Yuqin; Liu, Yufeng; Guo, Hongxiang; Xu, Xiaoli (Frontiers in Physiology, 2017)
Background: NO is an important cellular signaling molecule which is derived from L-arginine by nitric oxide synthase (NOS) and the effects of NOS signaling in lung injury is conflicting. The present study was designed to observe the effect of NOS and Arginase signaling in the occurrence and development of lung injury and its mechanism. Methods: An ozone-stressed lung injury animal model was established by exposure to 2.0 ppm O3 for 30 min every day for consecutive 12 day with or without the administration of NO precursor L-arginine or non-selective NOS inhibitor N-nitro-L-arginine methyl ester (L-NAME). Then, the lung histological pathology, the releases of inflammatory mediators and the production of ROS were assayed by immunohistochemistry, ELISA and flow cytometry respectively. The activities and expression of NOS and Arginase were assayed by biochemical methods and western blot. Correspondingly, the release of 8-OxoG and OGG1 were assayed by ELISA and western blot. The correlation between NOS/Arginase signaling with 8-OxoG/ OGG1 was also analyzed by Pearson correlation coefficients and immunofluorences in NOS deficient bronchial epithelial cells. Results: In ozone-induced rat lung injury models, lung inflammation as well as lung architecture was disrupted in a time dependent manner. Ozone treatment with L-arginine showed a substantial attenuation of adverse lung histopathological changes and treatment with L-NAME promoted the inflammation and remodeling. Importantly, the expression of NOS was promoted by L-arginine and inhibited by L-NAME and the expression of Arginase was promoted by L-NAME treatment. Further, we observed significantly higher levels of 8-OxoG and lower levels of OGG1 in ozone group which was reversed by L-arginine and promoted by L-NAME. The expression of NOS is closely related with 8-OxoG /OCG1. Conclusion: These findings give further evidence that the NOS signaling is related with base excise repair.